C-reactive protein as an inflammatory marker of acute infections outside intensive care settings: case report and evidence-based literature review - Alcino Pires Gama; Itamar de Souza Santos; Rodrigo Diaz Olmos; Lucia Mendes de Oliveira Pinto; Isabela Judith Martins Benseñor; Paulo Andrade Lotufo (University of São Paulo, 2011)
We present the clinical case of a 76-year-old woman with delirium caused by multiple factors, including pneumonia. Although this type of case is quite common in clinical practice, it provides us with an opportunity to discuss laboratory testing in this context, with a special focus on the role of C-reactive protein (CRP). We present data regarding the requests for determination of serum CRP levels at the University of São Paulo University Hospital over the past few years. We also present a review of the medical literature on the topic, as well as clinical epidemiology concepts related to the impact that CRP testing has on the medical decision-making process.